Teaching of Mathematical Proof in Middle School Geometry: A Systematic Review of Technology-Enhanced Approaches - As Elly; Yusuf Hartono; Nyimas Aisyah; Hapizah (Program Studi Tadris Matematika Universitas Islam Negeri (UIN) Salatiga, 2026)
This study investigates approaches to teaching mathematical proof at the middle school level through a systematic literature review, focusing on a key challenge in mathematics education: the difficulty students face in transitioning from empirical to deductive reasoning. Mathematical proof is a foundational element of mathematical reasoning, yet many students struggle with this shift. This study synthesizes empirical research on instructional approaches, particularly those that integrate technology, such as dynamic geometry software, augmented reality (AR), and digital learning tools, to improve students' proof skills. Following the PRISMA 2020 protocol, a systematic review was conducted with searches in Scopus, Web of Science, ERIC, and Google Scholar for studies published between 2014 and 2025. Forty-two empirical studies met the inclusion criteria. The findings highlight that technology-enhanced approaches, especially the use of dynamic geometry software, significantly improve students' abilities in proof construction, validation, and reasoning compared to conventional methods. Furthermore, the study identifies common challenges faced by teachers, including limited pedagogical content knowledge and difficulties in guiding students through the transition to formal proof. The review underscores the need to integrate inquiry-based learning and technology tools to foster deeper understanding of proofs at the middle school level. The study’s contribution lies in synthesizing diverse instructional strategies and providing evidence-based insights for future educational practices. Implications for practice and future research are also discussed.